Optimization of blending and production processes considering origin mines and metallurgical units using linear programming rules. Issue 3 (4th May 2021) - Farghaly, Mohamed G.; Ali, Mahrous; Kim, Jong-Gwan
ABSTRACT: This paper discusses a model that can optimize plant operation by considering transportation cost and metallurgical assays. All boundary conditions were set using ore samples taken from different locations in the same mine. Transportation from the mine to milling plants, dumping areas, and leaching units is also analyzed. Transportation from the mill to the smelter depends on assay results to ensure market readiness. We hypothesize that the grade of the material varies according to its source because milling plants are built to process different types of ore. Mines and processing units may be far apart, and therefore, it is critical to optimize production. Previous studies have discussed mine production optimization but did not consider metallurgical plants. The proposed model merges all units of a production system to determine the optimal planning solution. Linear programming uses network formulations of planning problems to consider a combination of mining and metallurgy operations. This technology is useful for analyzing the combination of two major systems, and hence, the dual theory was used in formulating the problem. The final model was applied to minimize the costs of production and distribution. The study checked the optimality of the solution for accuracy and its use as an indicator for long-term planning.